2005
DOI: 10.1002/ijc.21107
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac corrects defective apoptosis and suppresses azoxymethane‐induced colonic oncogenesis in p53 knockout mice

Abstract: The acute apoptotic response to genotoxic carcinogens (AARGC) might be important for controlling the subsequent colonic mutational load and progression through oncogenesis. We have found previously that AARGC is p53-dependent with a gene-dosage effect, and that decreased AARGC in p53 1/2 and p53 2/2 mice is associated with increased susceptibility to carcinogen-induced oncogenesis. We tested the ability of sulindac to reverse these defects. The effect of sulindac on azoxymethane (AOM)-induced apoptosis was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
1
20
1
Order By: Relevance
“…In this study, we hypothesized that selenium intake exerts its anticarcinogenic effect by enhancing the acute apoptotic response to carcinogen-induced DNA damage (AARGC). This is an important mechanism for removing cells harboring oncogenic DNA adducts and is a regulatory target for a variety of dietary agents and drugs (22,23,(25)(26)(27)40). We found that AARGC in the colon was significantly enhanced in animals fed MPSe1 and CasYSe4 but not in animals fed CasYSe1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we hypothesized that selenium intake exerts its anticarcinogenic effect by enhancing the acute apoptotic response to carcinogen-induced DNA damage (AARGC). This is an important mechanism for removing cells harboring oncogenic DNA adducts and is a regulatory target for a variety of dietary agents and drugs (22,23,(25)(26)(27)40). We found that AARGC in the colon was significantly enhanced in animals fed MPSe1 and CasYSe4 but not in animals fed CasYSe1.…”
Section: Discussionmentioning
confidence: 99%
“…The colons were scored for macroscopically visible tumors. Tumors were dissected, embedded in paraffin, and stained by H&E for histopathologic evaluation to classify them as adenoma and adenocarcinoma (23). Endpoints were colon tumor incidence (i.e., proportion of mice affected by a tumor), tumor multiplicity, tumor size, and number of mice with adenocarcinomas (cancers).…”
Section: Cancer Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Current treatment options for CRC include surgery, chemotherapy and radiation therapy, all of which can significantly reduce quality of life. Emerging therapeutic strategies for CRC include the nonsteroidal anti-inflammatory drug, Sulindac, 3 new chemotherapeutics including Capecitabine, 4 and antibodies such as the monoclonal epidermal growth factor receptor (EGFR) antibody, Cetuximab. 5 However, probiotics represent another emerging therapeutic option.…”
mentioning
confidence: 99%
“…With respect to the potential of dietary SM on preventing tumour initiation, our particular interest was to examine whether SM regulated the apoptotic response to DNA damage (AARGC), which is important for eliminating DNA-damaged cells during tumour initiation [35]. Our previous studies have shown that defective AARGC is associated with increased risk for CRC in p53 +/ -and p53 -/ -mice [28,29], and that up-regulation of AARGC by a variety of dietary agents and drugs is associated with protection for CRC [29, 35, 48 -52]. In keeping with earlier studies [5,34,47], our study showed that SM intake (0.05 -0.1%) did not affect baseline apoptosis.…”
Section: Discussionmentioning
confidence: 99%